Tort Law and State Accountability for Overseas Violations of International Human Rights Law and International Humanitarian Law: The UK Perspective - Grušić, Uglješa (Utrecht Journal of International and European Law, 2021)
This article argues that tort law has a role to play in holding the British government to account for overseas violations of international human rights law and international humanitarian law. The context of tortious claims for overseas violations of international human rights law and international humanitarian law brings to the fore, on one hand, issues of attribution and Crown and foreign acts of State and, on the other hand, issues of private international law. This article describes the approach of UK courts to key issues raised by tortious claims for overseas violations of international human rights law and international humanitarian law, namely subject-matter jurisdiction and the law applicable to the merits.